Upaya menumbuhkan karakter gemar membaca melalui gerakan literasi nasional - Dewi, Amelia (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2022)
Reading is a useful activity to add information, knowledge, and insight. If from an early age the children are trained and accustomed to reading, than the character of liking to read will grow in the children. All components of society can participate to increase the communitiy's literacy index by cultivating the character of liking to read. The purpose of this research is to identify various efforts that can be made to foster the character of liking to read in Indonesian society. The research method used is library research. The main data source used in this research is a collection of previous research journal articles and books that are relevant to the research discussion. The results of the research show that the literacy index of Indonesian people is still quite lacking, efforts that can be made to improve the literacy index can be through learning, exemplary, strengthening, and habituation. In addition, parents or teachers can use the storytelling method in order to attract children's attention and interest to read. These efforts can be done as early as possible in order to grow into a strong characters and not be carried away by the swift currents of technology and globalization.